2023
DOI: 10.1177/08997640231174837
|View full text |Cite
|
Sign up to set email alerts
|

Charity and Abuse: Fundraising and Symbolic Power in the Case of Jimmy Savile

Abstract: In life, Jimmy Savile was revered as Britain’s greatest charity fundraiser. In death, he is remembered as Britain’s most notorious pedophile. Raising over £40 million for good causes throughout his media career, a year after his death several investigations revealed a history of abuse of hundreds of children, mostly young girls, across the institutions he worked or volunteered at. Using the framework of the symbolic power of charity, this article documents how these crimes were either missed or covered up. Sav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Equally, we can imagine someone whose philanthropy is having an impact, but they are doing it for the wrong reasons, or are engaging in other activities, which may cause greater harm than any good they do through giving. An extreme case of this, as detailed by Jon Dean (2023), is the former UK TV personality Jimmy Savilewho was renowned as a charity donor and fundraiser during his lifetime, but is now known to have been a horrific and prolific sexual predator who deliberately used the "good glow" of charity to mask his activities.…”
Section: The Ethics and Morality Of Beast Philanthropymentioning
confidence: 99%
“…Equally, we can imagine someone whose philanthropy is having an impact, but they are doing it for the wrong reasons, or are engaging in other activities, which may cause greater harm than any good they do through giving. An extreme case of this, as detailed by Jon Dean (2023), is the former UK TV personality Jimmy Savilewho was renowned as a charity donor and fundraiser during his lifetime, but is now known to have been a horrific and prolific sexual predator who deliberately used the "good glow" of charity to mask his activities.…”
Section: The Ethics and Morality Of Beast Philanthropymentioning
confidence: 99%
“…But if something exists in wider society, it exists in the charity sector. The Oxfam sexual abuse (Gillespie et al, 2019) and President's Club harassment scandals, alongside Jimmy Savile's numerous crimes (Dean, 2023), showed that the #metoo conversation needed to be happening in the charity sector as well, as many female practitioners had intimated for decades. Yet because of the sector's position as 'special' and 'different', these complexities have been ignored or glossed over-that specialness often used as a mask for bullying and poor practice (Dean, 2020).…”
Section: On Charity and Sexmentioning
confidence: 99%